Developing a conceptual framework for interdisciplinary communication, collaboration, and integration: A structured approach - Jialin Zhang; Hanna Salomon; Martin Nicola Huber; Harald Bugmann; Julie Elisabet Dölker; Louis König; Jasmin Krähenbühl; Eva Lieberherr; Ivana Logar; Brian McArdell; Peter Molnar; Simone Quatrini; et al. (Ambio, 2025)
Interdisciplinary research is essential to address the complex environmental challenges faced by social-ecological systems (SES). However, it is often hindered by difficulties in integrating diverse knowledge and perspectives. Conceptual Frameworks (CFs) can act as boundary objects, facilitating integration in contexts with incomplete knowledge, nonlinearity, and divergent interests. Yet, guidance on developing CFs remains limited. To address this gap, we develop a structured approach and apply it within a research project focused on enhancing the resilience of Swiss Alpine ecosystems. Our approach includes three phases: (1) defining boundary concepts, (2) developing a CF as a boundary object, and (3) using the CF as a boundary object. The resulting CF supports communication, collaboration, and integration across disciplines, advancing SES research that addresses ecological resilience and sustainability. Our approach can be used by other interdisciplinary teams aiming to develop adaptable CFs that facilitate knowledge integration across disciplines.

Age and body mass index are associated with dorsolateral prefrontal cortex activation in response to unhealthy food cues - Floor van Meer; Laura N. van der Laan; Gabriele Eiben; Lauren Lissner; Maike Wolters; Stefan Rach; Manfred Herrmann; Peter Erhard; Denes Molnar; Gergely Orsi; Roger A.H. Adan; Paul A.M. Smeets (Appetite, 2025)

Operator exposure and cabin protection in plant protection product application - Gabor Molnar; Katrin Ahrens; Jens Karl Wegener; Sebastian Dittmar; Enrico Peter; Sabine Martin; Jan-Niklas Schäckermann; Markus Röver (Journal of Consumer Protection and Food Safety, 2025)
Tightly sealed driver's cabs can effectively protect the user from exposure when applying crop protection products. Therefore, under certain conditions, users in such cabins can avoid wearing personal protective equipment for skin and eyes. The protective effect depends on the technical design and handling of the different cabin types and can be divided into categories with different levels of protection. Since the level of protection of the different types of cabins and the associated possibility of not wearing personal protective equipment has not been sufficiently scientifically verified in the past, the present study was carried out to close this gap. Field and laboratory test methods were developed and used to assess exposure levels. External contamination of the cabin was measured using various dosimeters. Exposure inside the cabins was measured on coveralls and gloves to measure dermal exposure and with aerosol sampling pumps to determine inhalation exposure. Tests were conducted on tractors with different cab categories using an air-assisted orchard sprayer as a worst-case scenario for exposure to spray drift. Additionally, an alternative laboratory test method was developed and conducted to evaluate filter efficiency under controlled conditions and compare it with the field tests. The results showed that exposure inside closed cabins was generally low and was not notably correlated with the cabin category. All types of cabins tested were found to provide significant protection from dermal and inhalation exposure.

Investigating suspended sediment dynamics in the Spöl and Inn rivers during experimental floods using high-resolution monitoring - Jessica Droujko; Jan Martini; Peter Molnar (Journal of Environmental Management, 2025)

Current and future cropland suitability for cereal production across the rainfed agricultural landscapes of Ethiopia - Mosisa Tujuba Wakjira; Nadav Peleg; Johan Six; Peter Molnar (Agricultural and Forest Meteorology, 2024)

Location, location, location–A study of factors affecting air quality in Swedish preschool yards - Jenny Lindén; Mehjar Azzouz; Leonard Stockfelt; Malin Gustafsson; Peter Molnar; Malva Laurelin; Johanna Rieck Jildén; Helene Olofson; Ågot K. Watne (Sustainable Cities and Society, 2024)

Unveiling the future water pulse of central asia: a comprehensive 21st century hydrological forecast from stochastic water balance modeling - Tobias Siegfried; Aziz Ul Haq Mujahid; Beatrice Marti; Peter Molnar; Dirk Nikolaus Karger; Andrey Yakovlev (Climatic Change, 2024)

Novel field data for exposure of bystanders and residents towards spray drift during application of plant protection products in orchards - Katrin Ahrens; Markus Röver; Gabor Molnar; Sabine Martin; Enrico Peter; Jan-Niklas Schäckermann; Sandra Bense; Jens Karl Wegener (Journal of Consumer Protection and Food Safety, 2024)
Exposure to pesticide spray drift during the application of plant protection products (PPP) in orchards poses potential health risks to bystanders and residents. To address this concern, this study aimed to gather novel field data on exposure to spray drift in orchards. The research was conducted by the Julius Kuehn-Institute (JKI), the Federal Office of Consumer Protection and Food Safety (BVL), and the German Federal Institute for Risk Assessment (BfR). From 2018 to 2021, the method for conducting the field trials and analysis was implemented. The data from multiple series of performed field trials conducted between 2021 and 2022 allowed for collecting data on potential dermal exposure (PDE), inhalation exposure, and ground sediment. The trials considered various distances from the treatment area and drift-reducing techniques. Adult and child mannequins were used to simulate bystanders’ exposure, and petri dishes were used to measure ground sediment. The results showed that drift reduction settings (75% drift reduction) considerably reduced exposure levels on the mannequins. Furthermore, a strong correlation between PDE values for adults and children located next to each other at the same distance was observed. This finding suggests a possibility to convert exposure results from adult to child mannequins. The study produced realistic exposure data for bystanders and residents next to a treated area. It contributes to a better understanding of exposure risks from PPP application and includes data for different distances and spray drift reducing technique. If taken into account for further development of the current risk assessment models, new risk management options for the safe application of PPP, including buffer strips or application of drift reducing systems, might be available in near future.

Mitochondrial dysfunction in long COVID: mechanisms, consequences, and potential therapeutic approaches - Tihamer Molnar; Andrea Lehoczki; Monika Fekete; Reka Varnai; Laszlo Zavori; Szabina Erdo-Bonyar; Diana Simon; Tímea Berki; Peter Csecsei; Erzsebet Ezer (GeroScience, 2024)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has introduced the medical community to the phenomenon of long COVID, a condition characterized by persistent symptoms following the resolution of the acute phase of infection. Among the myriad of symptoms reported by long COVID sufferers, chronic fatigue, cognitive disturbances, and exercise intolerance are predominant, suggesting systemic alterations beyond the initial viral pathology. Emerging evidence has pointed to mitochondrial dysfunction as a potential underpinning mechanism contributing to the persistence and diversity of long COVID symptoms. This review aims to synthesize current findings related to mitochondrial dysfunction in long COVID, exploring its implications for cellular energy deficits, oxidative stress, immune dysregulation, metabolic disturbances, and endothelial dysfunction. Through a comprehensive analysis of the literature, we highlight the significance of mitochondrial health in the pathophysiology of long COVID, drawing parallels with similar clinical syndromes linked to post-infectious states in other diseases where mitochondrial impairment has been implicated. We discuss potential therapeutic strategies targeting mitochondrial function, including pharmacological interventions, lifestyle modifications, exercise, and dietary approaches, and emphasize the need for further research and collaborative efforts to advance our understanding and management of long COVID. This review underscores the critical role of mitochondrial dysfunction in long COVID and calls for a multidisciplinary approach to address the gaps in our knowledge and treatment options for those affected by this condition.

PM2.5 in Cape Town, South Africa: Chemical characterization and source apportionment using dispersion-normalised positive matrix factorization - Anna Alfeus; Peter Molnar; Johan Boman; Philip K. Hopke; Janine Wichmann (Atmospheric Pollution Research, 2024)

Increased erosion in a pre-Alpine region contrasts with a future decrease in precipitation and snowmelt - Tabea Cache; Jorge A. Ramirez; Peter Molnar; Virginia Ruiz-Villanueva; Nadav Peleg (Geomorphology, 2023)

Long-term ambient air pollution and venous thromboembolism in a population-based Swedish cohort - Mehjar Azzouz; Yiyi Xu; Lars Barregard; Bengt Zöller; Peter Molnar; Anna Oudin; Mårten Spanne; Gunnar Engström; Leo Stockfelt (Environmental Pollution, 2023)

Particulate Matter (PM2.5) Characterization, Air Quality Level and Origin of Air Masses in an Urban Background in Pretoria - Adewale Adeyemi; Peter Molnar; Johan Boman; Janine Wichmann (Archives of Environmental Contamination and Toxicology, 2022)

Source apportionment of fine atmospheric particles using positive matrix factorization in Pretoria, South Africa - Adewale Adeyemi; Peter Molnar; Johan Boman; Janine Wichmann (Environmental Monitoring and Assessment, 2021)

Implementation of personalized medicine in Central-Eastern Europe: pitfalls and potentials based on citizen’s attitude - Peter Balicza; Andras Terebessy; Zoltan Grosz; Noemi Agnes Varga; Aniko Gal; Balint Andras Fekete; Maria Judit Molnar (EPMA Journal, 2018)

Comparative survey of canine parvovirus, canine distemper virus and canine enteric coronavirus infection in free-ranging wolves of central Italy and south-eastern France - Barbara Molnar; Christophe Duchamp; Karin Möstl; Peter-Allan Diehl; Bruno Betschart (European Journal of Wildlife Research, 2014)

Pacific Ocean sea-surface temperature variability and predictability of rainfall in the early and late parts of the Indian summer monsoon season - Balaji Rajagopalan; Peter Molnar (Climate Dynamics, 2012)

Modelling river and riparian vegetation interactions and related importance for sustainable ecosystem management - Paolo Perona; Carlo Camporeale; Eliana Perucca; Maurizio Savina; Peter Molnar; Paolo Burlando; Luca Ridolfi (Aquatic Sciences, 2009)

An experimental comparison of silica gel and quartz sand grains as sediment media for growing vegetation at the laboratory scale - Zhe Jiang; Paolo Perona; Robert Francis; Peter Molnar; Paolo Burlando (Aquatic Sciences, 2009)

Expression of PACAP-Like Compounds During the Caudal Regeneration of the Earthworm Eisenia fetida - Eszter Varhalmi; Ildiko Somogyi; Gabor Kiszler; Jozsef Nemeth; Dora Reglodi; Andrea Lubics; Peter Kiss; Andrea Tamas; Edit Pollak; Laszlo Molnar (Journal of Molecular Neuroscience, 2008)

Changes in the Expression of PACAP-like Compounds During the Embryonic Development of the Earthworm Eisenia fetida - Akos Boros; Dora Reglodi; Zsofia Herbert; Gabor Kiszler; Jozsef Nemeth; Andrea Lubics; Peter Kiss; Andrea Tamas; Seiji Shioda; Kouhei Matsuda; Edit Pollak; Laszló Molnar (Journal of Molecular Neuroscience, 2008)

Electrophysiological and immunocytochemical characterization of DRG neurons on an organosilane surface in serum-free medium - Jie Liu; John W. Rumsey; Mainak Das; Peter Molnar; Cassie Gregory; Lisa Riedel; James J. Hickman (In Vitro Cellular & Developmental Biology - Animal, 2008)

Adult rat spinal cord culture on an organosilane surface in a novel serum-free medium - Mainak Das; Neelima Bhargava; Cassie Gregory; Lisa Riedel; Peter Molnar; James J. Hickman (In Vitro Cellular & Developmental Biology - Animal, 2005)

ADULT RAT SPINAL CORD CULTURE ON AN ORGANOSILANE SURFACE IN A NOVEL SERUM-FREE MEDIUM - MAINAK DAS; NEELIMA BHARGAVA; CASSIE GREGORY; LISA RIEDEL; PETER MOLNAR; JAMES J. HICKMAN (In Vitro Cellular & Developmental Biology - Animal, 2005)

Adult Rat Spinal Cord Culture On An Organosilane Surface In A Novel Serum-Free Medium - Mainak Das; Neelima Bhargava; Cassie Gregory; Lisa Riedel; Peter Molnar; James Hickman (In Vitro Cellular & Developmental Biology - Animal, 2005)

The Sum Is Greater than the Parts - JENNIFER MOLNAR; MICHELLE MARVIER; PETER KAREIVA (Conservation Biology, 2004)